Metalated graphene nanoplatelets and their uses as anode materials for lithium-ion batteries. (17th November 2016) - Xu, Jiantie; Jeon, In-Yup; Choi, Hyun-Jung; Kim, Seok-Jin; Shin, Sun-Hee; Park, Noejung; Dai, Liming; Baek, Jong-Beom
Abstract: A series of post-transition metals and semimetals in groups IIIA (Al, Ga, In), IVA (Ge, Sn, Pb) and VA (As, Sb, Bi) were introduced onto graphene nanoplatelets (GnPs) by mechanochemical reaction. The selected metals have a lower electronegativity ( χ, 1.61 ≤  χ M  ≤ 2.18) but a much larger covalent atomic radius ( d M  = 120–175 pm) than carbon ( χ C  = 2.55, d C  = 77 pm). The effect of the electronegativity and atomic radius of the metalated GnPs (MGnPs, M = Al, Ga, In, Ge, Sn, Pb, As, Sb, or Bi) on the anode performance of lithium-ion batteries was evalusted. Among the series of prepared MGnPs, GaGnP ( χ Ga  = 1.81, d Ga  = 135 pm) in group IIIA, SnGnP ( χ Sn  = 1.96, d Sn  = 140 pm) in group IVA and SbGnP ( χ Sb  = 2.05, d Sb  = 141 pm) in group VA exhibited significantly enhanced performance, including higher capacity, rate capability and initial Coulombic efficiency. Both the experimental results and theoretical calculations indicated that the optimum atomic size ( d M  ∼ 140 pm) was more significant to the anode performance than electronegativity, allowing not only efficient electrolyte penetration but also fast electron and ion transport across the graphitic layers.